Cytotoxicity of 1-Aryl-3-buthylamino-1-propanone Hydrochlorides against Jurkat and L6 Cells - Gul, Mustafa; Mete, Ebru; Atalay, Mustafa; Arik, Mustafa; Gul, Halise Inci (Arzneimittelforschung, 2009)
1-Aryl-3-buthylamino-1-propanone hydrochloride type mono Mannich bases were synthesized and their cytotoxicity was tested against transformed human T-lymphocytes (Jurkat cells) and rat skeletal muscle derived myoblasts (L6 cells). Aryl part was changed as phenyl in 1, 4-methylphenyl in 2, 4-chlorophenyl in 3, 4-fluorophenyl in 4, 4-bromophenyl in 5, 4-hydroxyphenyl in 6, 2-acethylthiophene in 7. Of the compounds synthesized, 2, 5, 6, and 7 are reported for the first time. Compounds 1–7 had 3.16, 3.13, 3.35, 2.87, 4.17, 2.60, and 3.04 times higher cytotoxic potency than the reference compound 5-fluorouracil (CAS 51-21-8) against Jurkat cells, respectively. Compounds 1, 3, 4, 5, 6, and 7 had 1.22, 1.46, 1.59, 2.18, 1.24, and 1.45 times higher cytotoxic potency than the reference compound 5-fluorouracil against L6 cells, respectively. Among the compounds tested, only compound 5 had almost equal cytotoxic potency with the reference compound melphalan (CAS 148-82-3) against Jurkat and L6 cells. All compounds synthesized showed higher cytotoxic activity against Jurkat cells compared with L6 cells. Specifically, compounds 1−7 had 2.05, 2.68, 1.82, 1.43, 1.51, 1.66, and 1.66 times higher cytotoxicity against Jurkat cells compared with L6 cells. In Jurkat cells, there was a significant negative correlation between Log P and IC50 values (correlation coefficient: −0.955, p = 0.03), which actually means a positive correlation between the Log P and the cytotoxic activity of the compounds. These results suggest that the most potent compound 5 (a 4-bromo derivative) against both cell lines may serve as a model compound to develop new cytotoxic agents for further studies.
Keywords: Buthylamine acetophenones, synthesis; Cytotoxic agents; Jurkat cells; L6 cells; Mannich bases